Kesenjangan Rantai Pasok Kelapa Sawit di Lanskap Ketungau Kabupaten Sintang Provinsi Kalimantan Barat - Supriyanto Supriyanto; Agus Ruliyansyah; Muhammad Pramulya; Nur Arifin; Henny Sulistyowati (Perkebunan dan Lahan Tropika, 2021)
Oil palm supply chain gaps in the Ketungau landscape of Sintang district, West Kalimantan province. The development of oil palm plantations in Sintang Regency has been rapid in the last decade. Sintang Regency has declared to implement sustainable oil palm plantations while still considering environmental sustainability aspects. Management of the oil palm trading system to be effective and efficient is the main indicator of sustainable oil palm plantations. Gap analysis in the trading system is an important effort as a basis for making various policies. The Gap Analysis of Oil Palm Supply Chain in the Ketungau Landscape, Sintang Regency, West Kalimantan Province is aimed to identify the gaps that occur between levels of oil palm trading actors in the Ketungau Landscape, Sintang Regency. The analysis is carried out using a comparison method between the current reality and the perspectives expected by the stakeholders. The results of the analysis show that in the palm oil supply chain in the Ketungau Landscape, gaps still occur at every level of the supply chain. The gap between independent oil palm smallholders and the government is the lack of assistance programs and capacity building for smallholders and improving the quality of infrastructure. The gap between the government and companies is that the government's supervision of palm oil business actors is still not maximal. The gap between independent smallholders and companies is that there is still no understanding between the two parties, especially regarding the quality criteria for FFB. The results of this study indicate that independent oil palm farmers in the Ketungau Landscape still require policy intervention from the government and oil palm companies.